2015
DOI: 10.1021/acs.jpcb.5b01977
|View full text |Cite
|
Sign up to set email alerts
|

Sequence-Dependent Solvation Dynamics of Minor-Groove Bound Ligand Inside Duplex-DNA

Abstract: Ligand binding to minor-grooves of DNA depends on DNA-base sequence near its binding-site. However, it is not known how base-sequences affect the local solvation of ligand inside minor-grooves of DNA. Here we present a comprehensive study on sequence-dependent solvation dynamics of ligand inside duplex-DNA by measuring the static and dynamic fluorescence Stokes shifts of a popular groove-binder, DAPI, inside DNA minor-grooves created by four different sequences; d(5'-CGCGAATTCGCG-3')2, d(5'-CGCGTTAACGCG-3')2, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
51
0

Year Published

2016
2016
2021
2021

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 21 publications
(51 citation statements)
references
References 75 publications
0
51
0
Order By: Relevance
“…Recently, our group have shown that the dynamic Stokes shift of groove-bound DAPI in duplex DNA follows a similar power law until ~100 ps-although beyond 100 ps the dynamics converge to equilibrium through exponential relaxations [11,12]. It has also been shown that such dynamics are modulated by the change in base sequences near the DAPI binding site [13]. However, it was not known how the dynamics of solvation occur in higher order GqDNA structures until our group reported the first study of the dynamic Stokes shift of groove-bound DAPI in antiparallel hTelo22 GqDNA [19].…”
Section: Introductionmentioning
confidence: 98%
See 1 more Smart Citation
“…Recently, our group have shown that the dynamic Stokes shift of groove-bound DAPI in duplex DNA follows a similar power law until ~100 ps-although beyond 100 ps the dynamics converge to equilibrium through exponential relaxations [11,12]. It has also been shown that such dynamics are modulated by the change in base sequences near the DAPI binding site [13]. However, it was not known how the dynamics of solvation occur in higher order GqDNA structures until our group reported the first study of the dynamic Stokes shift of groove-bound DAPI in antiparallel hTelo22 GqDNA [19].…”
Section: Introductionmentioning
confidence: 98%
“…The hydration dynamics around these biomolecules, perturbed by them, facilitate many important biochemical processes such as protein folding [3], enzyme catalysis [4], DNA-protein [5,6] and DNAligand interactions [7,8]. In fact, such hydration dynamics, coupled with biomolecular and counterion motion, can give rise to the dispersed dynamics of solvation in DNA and proteins [9][10][11][12][13][14][15][16][17][18][19][20][21][22]. However, this effect is found to be significant in DNA [9][10][11][12][13][14][15][16][17][18][19], possibly because of the complex coupled motions of charged DNA, water and ions, which on most occasions show dispersed solvation dynamics from femtoseconds to nanoseconds, inherently following a power law relaxation [9][10][11][12][13][14][15][16].…”
Section: Introductionmentioning
confidence: 99%
“…The Fee‐Maroncelli protocol requires recording the absorption spectrum of the ER‐Tracker dye, which is almost impossible under a few molecules condition in a live cell. Recently, Sen and co‐workers suggested that ν (0) and hence the missing component of solvation may be obtained from recording absorption spectra of the solvation probe in a rigid matrix at low temperature . However, this method is also not applicable in our case, because it is doubtful whether the micro‐environment of the ER region would be the same when a live cell is frozen.…”
Section: Resultsmentioning
confidence: 94%
“…Previous investigations of DNA solvation dynamics were performed with probes placed inside the duplex-DNA either by covalent attachment or by non-covalent minor groove binding. 36 The characterized dynamics in DNA were found to be nonexponential and extended into subpicosecond to nanoseconds timescales, best described by a power-law relaxation. 37 There is no unified explanation of such dispersed dynamics primarily because of the complicated coupling between motions of components localized in the closest (<1 nm) vicinity of the probe: water molecules, segments of the DNA molecule as well as cations.…”
Section: Resultsmentioning
confidence: 98%
“… 37 , 40 However, in all these cases, except for HNF, a minor, but significant nanosecond component is present. 36 , 41 …”
Section: Resultsmentioning
confidence: 99%